2014
DOI: 10.1007/s11012-014-9916-y
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach to invariants of plane elasticity tensors

Abstract: The action of the orthogonal group on the space of plane elasticity tensors has been the subject of some recent investigations. It is shown here that the approach based on the "harmonic decomposition" technique, which is also used in a three-dimensional setting, gives a unified perspective on this issue. We construct explicit relationships between invariants and quantities derived from such an approach and what was found earlier by Tsai and Pagano and, more recently, through the "polar method" and the use of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…It has been demonstrated that in 2D, there is only 4 different possibilities for the symmetry class of an elasticity tensor ( Forte and Vianello, 2014;He and Zheng, 1996;Vianello, 1997 ):…”
Section: Symmetry Classes and Stratamentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that in 2D, there is only 4 different possibilities for the symmetry class of an elasticity tensor ( Forte and Vianello, 2014;He and Zheng, 1996;Vianello, 1997 ):…”
Section: Symmetry Classes and Stratamentioning
confidence: 99%
“…6 This is achieved through a two-step process ( Forte and Vianello, 2014;Itin and Hehl, 2013;2014;Vianello, 1997 ):…”
Section: Irreducible Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analog problem in plane elasticity for the elasticity tensor in bidimensional space under the action of the orthogonal group O(2) has already been solved by numerous authors [89,44,14,90,37,7]).…”
Section: Introductionmentioning
confidence: 99%